Effectiveness of Intralesional Triamcinolone in the Treatment of Keloids in Children. Issue 1 (January 2016) - Acosta, Silvana; Ureta, Ester; Yañez, Ricardo; Oliva, Natalia; Searle, Susana; Guerra, Claudio
Abstract: Background: The current treatment of keloids includes surgery, intralesional steroids, and radiotherapy, among others. Radiotherapy is not recommended in children due to its effects on growing tissues. Our aim was to study intralesional triamcinilone therapy of keloids in children and analyze the impact of body location, age of the lesion, and etiology of the keloid on clinical response. Methods: We conducted a prospective clinical trial with patients 1 to 14 years of age evaluated for keloid treatment. A soft tissue ultrasound was performed to measure the keloid volume, prior to intralesional infiltration with triamcinolone acetonide. A posttreatment ultrasound quantified the volume differences attributed to therapy. For the analysis, Mann–Whitney/Wilcoxon test for paired samples and a multiple regression analysis were performed. Results: Twenty‐one patients with a total of 25 keloids were enrolled, with a median age of 12 years (range 6–14 yrs). The initial lesional volume was 1.25 cc (range 0.2–6.3 cc) and the final volume was 0.2 cc (range 0.0–1.53 cc), corresponding to 82.7% of size reduction (p < 0.001). Regarding the relationships between response and body location, etiology and age of the lesion, the multiple regression analyses obtained p‐values of 0.46, 0.16, and 0.87, respectively. One patient failed to improve. Average follow‐up was 30 months. Conclusions: Triamcinolone acetonide is highly effective for the treatment of pediatric keloids. There is no relationship between clinical response and the factors evaluated, such as lesion location, etiology and age of the keloid.